Immune status changes and URTI incidence in the initial 7 weeks of a winter training season in Portuguese swimmers - Rama, L. M.; Alves, F.; Rosado, F.; Azevedo, S.; Matos, A.; Henriques, A.; Paiva, A.; Teixeira, A. M. (Biomechanics and Medicine in Swimming XI, 2010)
increase of training load in the first mesocycle of the season. Swimmers often come back from off training periods unfit, so this option could result in a maladaptation condition with impact on the work capacity and health of the athletes. This study focused on the variation of hormonal and immune markers, and in the occurrence of upper respiratory tract infection symptoms (URTIS) registered during the first mesocyce of preparation, of a winter season, in a group of male swimmers. Results show that the higher rate of URTIS of the training season occurred in this period. At rest, an increase in leukocyte counts and a decrease in CD4+, CD8+ and NK cell counts were found. The increased serum cortisol levels and the decrease in the testosterone/cortisol ratio, could lead to a diminished immune competence observed.